Long-Run Movement and Predictability of Bond Spread for BRICS and PIIGS: The Role of Economic, Financial and Political Risks# - Chow, Sheung-Chi; Gupta, Rangan; Suleman, Tahir; Wong, Wing-Keung (Journal of Reviews on Global Economics, 2019)
We examine co-movement and predictability of Bond Spread of BRICS and PIIGS with respect to political risk (PR), financial risk (FR), and economic risk (ER). Our linear Granger causality findings imply that PR is the most important risk in predicting bond spread, followed by ER in both BRICS and in PIIGS, while FR is useful in predicting bond spread in BRICS only. Our nonlinear individual causality results infer that ER is the most important risk in predicting bond spread, followed by FR, and PR. We make a conjecture that linear and nonlinear causality are independent and our findings support this.